27.3: Synergistic Improvement of Photoresistance Adhesion for Cu Triple‐Layer Structure. (24th February 2021) - Tan, Minli; Liu, Jian; Hu, Xiaobo; Liu, Linfeng; Zhang, Jing; Zhang, Conglong
Abstract : In this work, we provide a rational strategy to synergistically improve the photoresistance adhesion of Cu triple‐layer structure. By using plasma treatment, the microporous structure can be formed on the surface of Cu triple‐layer, which increases the interface contact area. Subsequent wet chemical treatment can effectively increase the hydrophobic groups and improve the interface properties of Cu triple‐layer.